2012
DOI: 10.1172/jci59227
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Kras is required for both the initiation and maintenance of pancreatic cancer in mice

Abstract: Pancreatic cancer is almost invariably associated with mutations in the KRAS gene, most commonly KRAS G12D , that result in a dominant-active form of the KRAS GTPase. However, how KRAS mutations promote pancreatic carcinogenesis is not fully understood, and whether oncogenic KRAS is required for the maintenance of pancreatic cancer has not been established. To address these questions, we generated two mouse models of pancreatic tumorigenesis: mice transgenic for inducible Kras G12D , which allows for inducible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
667
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 674 publications
(697 citation statements)
references
References 66 publications
26
667
2
2
Order By: Relevance
“…The recent observation that activating KRAS mutations were present in >90% of pancreatic PanIN-1 lesions suggests that the acquisition of KRAS mutations likely precedes the formation of these precursor lesions (36). In addition to its role in tumor initiation, oncogenic KRAS is also required for PDAC maintenance (37). Despite its well-known role in cancer, development of drugs targeting KRAS directly has been unfruitful, underscoring the need for alternative approaches (3).…”
Section: Discussionmentioning
confidence: 99%
“…The recent observation that activating KRAS mutations were present in >90% of pancreatic PanIN-1 lesions suggests that the acquisition of KRAS mutations likely precedes the formation of these precursor lesions (36). In addition to its role in tumor initiation, oncogenic KRAS is also required for PDAC maintenance (37). Despite its well-known role in cancer, development of drugs targeting KRAS directly has been unfruitful, underscoring the need for alternative approaches (3).…”
Section: Discussionmentioning
confidence: 99%
“…21,22 The functional importance of mutant Kras, a member of the GTPase enzyme family, in pancreatic cancer, even in the setting of metastatic disease, has been shown in a series of seminal papers. [23][24][25] Consequently, the finding by Sureban and coworkers that siRNA-mediated knockdown of Dclk1 in human pancreatic cancer cells resulted in downregulation of Kras expression was of great interest. 19 The authors followed up this study with a more in depth analysis of pancreatic cancer cells with reduced Dclk1 gene expression, and demonstrated that Dclk1 regulated pluripotency and angiogenic programs via distinct miRNAs.…”
Section: Functional Relevance Of Dclk1 Expression In Malignancymentioning
confidence: 99%
“…Certain genetic studies have shown that K-Ras activation and mutation is necessary for the initiation of PC (26)(27)(28), and an inducible pancreas-specific expression system was used to show that K-Ras expression is also required for tumor maintenance (29). These mutations lock K-Ras and its downstream proteins, such as Akt and Erk, in a constitutively activated form.…”
Section: Discussionmentioning
confidence: 99%